OP4 Assessing the impact of the barbados sugar sweetened beverage tax on grocery store beverage sales and national imports: an interrupted time series analysis. (September 2018) - Alvarado, MA; Unwin, N; Sharp, S; Hambleton, I; Murphy, MM; Samuels, TA; Suhrcke, M; Adams, J; ,
Abstract : Background: A 10% tax on sugar sweetened beverages (SSBs) was implemented in Barbados in September 2015. This study aims to assess whether sales of SSBs and non-SSBs changed following implementation of the tax. Methods: We used electronic sales data from a major grocery chain from January 2012 – January 2017, and national import data from the Barbados Statistical Service from January 2013-July 2017. Grocery store data were used to calculate litres sold per week of SSBs, non-SSBs, and beverage sub-categories (sodas, waters) over 264 weeks. We used an interrupted time series (ITS) design to assess whether the introduction of the tax was associated with a change in level and trend in sales. All analyses controlled for inflation, seasonality and tourism. Using national import data, we calculated cumulative litres imported (to account for stockpiling) by beverage category. We assessed whether the introduction of the tax was associated with a change in the trend of the cumulative litres imported. To enable comparison, we re-estimated the grocery store models separately for locally manufactured and imported beverages. STATA/SE 14.2 was used for all analyses. Results: In 2016 (the first full year of tax implementation), the average decrease in SSB grocery store sales was −2, 822 litres/week [95% CI −6, 397 to 752] compared to the estimated counterfactual without the tax. The change per week increased over time, with an average decrease from July 2016-December 2016 of −4, 349 litres/week [95% CI −8, 307 to −391]. Locally manufactured SSBs decreased by an average of −5, 814 litres/week [95% CI −8, 692 to −2, 936] and imported SSBs increased by an average 4277 litres/week [95% CI 2, 872 to 5682]. Non-SSB sales increased by 1954 litres/week [95% CI 507 to 3401], with water accounting for an average increase of 1435 litres/week [95% CI 393 to 2477]. Monthly SSB imports increased by 3 69 000 litres per month following the tax [95% CI 325, 000 to 4 13 000]. Non-SSB imports increased by 2 81 000 litres per month [95% CI 268, 000 to 294, 000]. Conclusion: The Barbados SSB tax was not associated with a reduction in SSB sales at this grocery store chain, although there is evidence of a reduction at the end of the study period. National data suggest that SSB imports (which may be cheaper) increased. The grocery store analysis also suggest that sales of imported SSBs increased, while locally manufactured SSBs decreased, suggesting that consumers may be substituting to imported beverages. A higher rate of tax may be needed to reduce consumption of SSBs.